Contraceptive Access Creates Positive Selection in Infant Health - James Flynn (Institute of Labor Economics (IZA), 2024)
This paper documents an important unintended consequence of expanding contraceptive access; namely that it creates positive selection in the health of the children being born. I use a family planning intervention which gave thousands of long-acting reversible contraceptives to reproductive-age women in the St. Louis metropolitan area as a source of plausibly exogenous variation in contraceptive access to demonstrate that it reduced the rates of both extremely preterm births and infant mortality. I use both a synthetic control and synthetic difference-in-differences design, with my most conservative estimates suggesting that this program led to reductions of 2.5 extremely preterm births and 1.3 infant deaths per 1,000 live births across St. Louis County, reductions of approximately 23% and 15% respectively. I find large reductions for both Black and White mothers, with Black mothers experiencing a greater reduction in magnitude, but smaller reductions as a percentage of the baseline rate.
Keywords: J13; I18; I12; 330; contraceptive access; infant mortality; preterm birth; family planning